2019
DOI: 10.1155/2019/9287121
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Immune Response in the Elderly: Is It Necessary to Develop a Vaccine againstNeisseria meningitidisfor the Aged?

Abstract: Literature reports the association between aging and decline in the immune system function. The elderly have a higher risk of developing infectious diseases and are often less responsive to vaccines that are effective in the young. The case fatality rate of invasive meningococcal disease is higher in the elderly; therefore, vaccination for this population should be evaluated. Although new vaccines have been developed against Neisseria meningitidis, there is still a need to evaluate a vaccine for those older th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In addition, the meta-analysis also showed that CFRs generally increased with age and were highest in the oldest age groups [ 90 ]. As such, older adults represent an unmet need for meningococcal vaccination because, as noted by Trezikowski de Lima et al [ 105 ] “given the increasing proportion of older people in the population and the high CFR of meningococcal disease in the elderly, it would be interesting to evaluate the insertion of these vaccines in the immunization programs for this age group…also, vaccines can generate other benefits, e.g. lower overall cost of healthcare”.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the meta-analysis also showed that CFRs generally increased with age and were highest in the oldest age groups [ 90 ]. As such, older adults represent an unmet need for meningococcal vaccination because, as noted by Trezikowski de Lima et al [ 105 ] “given the increasing proportion of older people in the population and the high CFR of meningococcal disease in the elderly, it would be interesting to evaluate the insertion of these vaccines in the immunization programs for this age group…also, vaccines can generate other benefits, e.g. lower overall cost of healthcare”.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] To control the pandemic and reduce the burden of COVID-19 worldwide, effective and safe COVID-19 vaccines are urgently needed. The response to vaccines is usually reduced in older adults because of immune senescence, [4][5][6][7] the age-related changes that affect many of the cellular and molecular elements of both the innate and adaptive immune systems. Therefore, testing the effectiveness of COVID-19 vaccines in this population is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Although IMD affects individuals of all ages, the highest incidence occurs in young children, with a second disease peak among adolescents and young adults [ 5 , 6 ]. The incidence is also high in the elderly population, the age group with the highest case fatality rate (CFR) [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%